Pengembangan Diri dan Pembiasaan dalam Pembelajaran “Bahasa” - Maksudin (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2015)
The Habituation in learning “language” is lessened trial and substantial in terms of mastery and language skills including mastery and Arabic language skills. Because the habituation is a basic requirement in the learning “language” itself. For language learners to be able to master the language being studied or taught in the learning needs of habituation and repetition continuously. On the other side of habituation, the language will have a positive influence on the development of language learners themselves. Therefore, the relation of the habituation in learning the language as an integral part of self-development for language learners. In this paper, the self-development approach used a humanistic approach. This approach is seen to have compatibility with habituation in language learning